2018
DOI: 10.1016/j.jrp.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and personality development over twenty years: Evidence from three longitudinal samples

Abstract: A physically inactive lifestyle is associated with maladaptive patterns of personality development over relatively short follow-up periods. The present study extends existing research by examining whether this association persists over 20 years. Participants (total N = 8,723) were drawn from the Wisconsin Longitudinal Study Graduates and Siblings samples and the Midlife in the United States Study. Controlling for demographic factors and disease burden, baseline physical inactivity was related to steeper declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…This conclusion may also have important consequences: (1) Other psychological mechanisms have to be considered responsible for the observed relationship between physical activity and creativity. It might be hypothesized that the personality trait openness to experiences may serve as a potentially mediating variable, because it goes along with creativity and physical activity 63 , 64 . (2) To promote creativity, the induction of PAA plus the engagement in physical activity separately might be more fruitful in contrast to one strategy alone.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion may also have important consequences: (1) Other psychological mechanisms have to be considered responsible for the observed relationship between physical activity and creativity. It might be hypothesized that the personality trait openness to experiences may serve as a potentially mediating variable, because it goes along with creativity and physical activity 63 , 64 . (2) To promote creativity, the induction of PAA plus the engagement in physical activity separately might be more fruitful in contrast to one strategy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that chronic illness, such as cancer, are associated with detrimental personality changes [73,74], it seems to be crucial to find interventions that can counterbalance such changes. If prior studies have found PA may prevent maladaptive personality development among people without chronic disease [75,76], no study has investigated the extent to which PA for patients with MBC may be associated with personality change. ABLE02 study will be the first to test the effect of PA interventions on personality traits development among MBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…This has been supported by numerous observational studies that examined associations between personality and health behaviors. In terms of physical activity, higher conscientiousness has been associated with more time spent in physical activity, physical inactivity was related to a steeper decline in conscientiousness, and lower neuroticism and higher conscientiousness were associated with more physical activity, less inactivity, and sedentary behavior (Allen, Magee, et al, 2017; Stephan et al, 2018; Sutin et al, 2016). Studies using Aβ PET in cognitively normal older adults have shown that higher levels of self-reported physical activity are associated with lower levels of Aβ (Brown, Peiffer, & Martins, 2013; Head et al, 2012; Liang et al, 2010; Okonkwo et al, 2014), consistent with the hypothesis that exercise modulates Aβ production and clearance through direct and indirect pathways.…”
Section: Discussionmentioning
confidence: 99%